Analysis of User Behavior of the Digital Korlantas Polri Application with Integrated UTAUT in the Community of East Java Province - Poerwanto, Annisaa Putri Prameswari; Hawwin Mardhiana; Alifiansyah Arrizqy Hidayat (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Currently, more and more agencies are developing their services by utilizing technology in the form of mobile applications, including the Republic of Indonesia Police agency, especially the Traffic Corps with its mobile application-based service called Digital Korlantas Polri. This research aims to identify what factors influence users' interests, behavior and intentions towards the National Police Traffic Corps Digital application by testing 10 variable hypotheses built from the integration of the Unified Theory of Acceptance and Use of Technology (UTAUT), Technology Acceptance Model (TAM), Theory models. of Planned Behavior (TPB) and Service Quality with the educational level factor proposed as a moderator. The results of this research show that Performance Expectancy and Effort Expectancy are the 2 main factors influencing Behavioral Intention. Other results show that factors such as Social Influence, Facilitating Conditions, and Perceived Risk have a negative influence where they can reduce the user's Behavioral Intention. Apart from that, the research results also show that Behavioral Intention and Word of Mouth can influence users to continue using this application and educational level factors have a negative influence on users' behavioral intention to continue using the application on an ongoing basis. Keywords: Unified Theory of Acceptance and Use of Technology, Theory of Planned Behavior, Technology Acceptance Model, Service